Investigation of Cysteine as an Activator of Side-Chain N→S Acyl Transfer and Tail-to-Side-Chain Cyclization - Castillo-Pazos, Durbis J.; Macmillan, Derek (Synlett, 2017)
N→S Acyl transfer is a popular method for the postsynthesis production of peptide Cα-thioesters for use in native chemical ligation and for the synthesis of head-to-tail cyclic peptides. Meanwhile thioester formation at the side chain of aspartic or glutamic acids, leading to tail-to-side-chain-cyclized species, is less common. Herein we explore the potential for cysteine to function as a latent thioester when appended to the side chain of glutamic acid. Initial insights gained through study of C-terminal β-alanine as a model for the increased chain length were ultimately applied to peptide macrocyclization. Our results emphasize the increased barrier to acyl transfer at the glutamic acid side chain and indicate how a slow reaction, facilitated by cysteine itself, may be accelerated by fine-tuning of the stereoelectronic environment.
Keywords: cyclic peptides; native chemical ligation; acyl transfer